2017
DOI: 10.1016/j.jid.2017.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of CXXC5 by a Competing Peptide Stimulates Hair Regrowth and Wound-Induced Hair Neogenesis

Abstract: The Wnt/β-catenin pathway has been implicated in hair follicle development and hair regeneration in adults. We discovered that CXXC-type zinc finger protein 5 (CXXC5) is a negative regulator of the Wnt/β-catenin pathway involved in hair regrowth and wound-induced hair follicle neogenesis via an interaction with Dishevelled. CXXC5 was upregulated in miniaturized hair follicles and arrector pili muscles in human balding scalps. The inhibitory effects of CXXC5 on alkaline phosphatase activity and cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…WIHN is dependent on epidermal Wnt/β-catenin signaling. WIHN can also be promoted by direct modulation of Wnt signaling components such as Wnt ligands Wnt7a [92] and Wls [93], or indirectly through its negative regulator CXXC-type zinc finger protein 5 (CXXC5) [94], or through an external stimulus triggering Wnt activation, such as FGF9 released from dermal γδ T cells [95] or TNF released from wound-infiltrating macrophages [96]. In addition, it has been shown that WIHN requires transient epithelial Msx2 expression [97] and can be inhibited by prostaglandin D2 through the receptor Gpr44 [98].…”
Section: Wound-induced Hair Follicle Neogenesis (Wihn)mentioning
confidence: 99%
“…WIHN is dependent on epidermal Wnt/β-catenin signaling. WIHN can also be promoted by direct modulation of Wnt signaling components such as Wnt ligands Wnt7a [92] and Wls [93], or indirectly through its negative regulator CXXC-type zinc finger protein 5 (CXXC5) [94], or through an external stimulus triggering Wnt activation, such as FGF9 released from dermal γδ T cells [95] or TNF released from wound-infiltrating macrophages [96]. In addition, it has been shown that WIHN requires transient epithelial Msx2 expression [97] and can be inhibited by prostaglandin D2 through the receptor Gpr44 [98].…”
Section: Wound-induced Hair Follicle Neogenesis (Wihn)mentioning
confidence: 99%
“…Peptides and some growth factors have also shown inhibitory effects on DPCs. In addition, certain other agents have exerted inhibition of DPCs activity in vitro .…”
Section: Hair Growth Inhibitory Effectmentioning
confidence: 99%
“…Aberrant Wnt signaling has been found to be associated with hair loss (alopecia) and anabolic osteoporosis. A previous study demonstrated that expression of CXXC5 is upregulated and is inversely correlated with that of β‐catenin in both haired and bald individuals . In mice, CXXC5 knockout or competitive peptide‐mediated disruption of the CXXC5‐Dvl interaction restores Wnt signaling and accelerates hair regrowth and wound‐induced hair follicle neogenesis .…”
Section: Pathophysiological Functions Of Cxxc5mentioning
confidence: 99%
“…A previous study demonstrated that expression of CXXC5 is upregulated and is inversely correlated with that of β‐catenin in both haired and bald individuals . In mice, CXXC5 knockout or competitive peptide‐mediated disruption of the CXXC5‐Dvl interaction restores Wnt signaling and accelerates hair regrowth and wound‐induced hair follicle neogenesis . Similarly, targeting the CXXC5‐Dvl interaction with small molecules has been suggested as a new therapeutic approach for the treatment of anabolic osteoporosis …”
Section: Pathophysiological Functions Of Cxxc5mentioning
confidence: 99%
See 1 more Smart Citation